PENGARUH BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) DAN NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSET (ROA) (Studi Kasus Pada Bank Swasta Yang Terdaftar Di Indonesia Stock Exchange Periode 2013-2023) - Br Siahaan, Putri; Prestarika Lukito, Cristine (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Operating Expenses, Operating Income (BOPO) and Non Performing Loan (NPL) on Return On Asset (ROA), both partially and simultaneously. The research method uses quantitative research methods with descriptive statistical analysis, classical assumption testing, and hypothesis testing and data processing using Eviews 12. The sample in this research in the company’s financials reports in the form of balance sheets, profit and loss and notes to financial reports consisting of the Private Bank Subsector for the 2013-2023 period. The results of this research show that: The Operational Expense Variable Operational Income partially has a significant effect on return On Assets. This is proven by the results of tcount > ttable (-6,6062 >1.68288) with a significant of 0.0000 < 0.05. The Non-performing Loan variable partially has a  significant effect on Return on Assets. This is proven by the results of tcount>ttable (-2,9578 > 1.68288) with a significane of 0.0051 < 0.05. Operational Expense variable operational Income and Non-Performing  Loans simultaneously have a significant effect on Return On Assets. This is proven by the results tcount>ftable (28,91242 > 3.22) with a significant of 0.000000 < 0.05. The coefficient of determination result in panel data is 56,48%, indicating that the BOPO and NPL, variables influence ROA while the remaining 43,52% is the influenced by other factor not wxplained in this research.